331 Implementation of Community Based Comprehensive Geriatric Assessment and Intervention in a Rural Irish Setting. (16th September 2019) - McLoughlin, Petra; Murphy, Eleanor; O'Sullivan, Fiona; Connellan, Ciara
Abstract: Background: The Integrated Care Team for Older People (ICTOP) in Sligo formed in 2018 to provide home based rehabilitation for acutely frail older adults to enable them to continue to live independently. It serves a predominantly rural catchment area with 14.5% aged >65 years versus the national average of 11%. 1 An in-home person-centred multi-disciplinary approach is utilized based on the principles of comprehensive geriatric assessment (CGA). This observational study aims to describe the typical user of this service, interventions and outcomes to date. Methods: An Excel database was compiled and analysed from CGA of consecutive referrals from June to December 2018. Results: Of the 70 referrals studied, 69% resided in rural Sligo, two thirds were female and there was a mean age of 82.3 (range 68-95). The median Rockwood Clinical Frailty Scale level was 6 and the median Timed Up and Go was 28seconds. Hospital in-patients accounted for 58% of referrals with functional deterioration (74%), mobility decline (72%) and cognitive decline (28%) the most frequent referral reasons. Gait imbalance was the most prevalent co-morbidity (77%). There was an average of 4.5 home visits per person. Over 80% of referrals received combined physiotherapy and occupational therapy input, with Clinical Nurse Specialist (CNS) in Dementia involvement in 40%, speech and language therapy in 26% and social work in 15%. CGA identified additional clinical and social needs in 100%, and the team made 217 onward referrals to available community health and social supports. ICTOP referral decreased length of stay by 2.6days and only one patient required long term care. Conclusion: The use of a multidisciplinary team providing domiciliary assessments decreased hospital stay, facilitated maintenance of independent living and addressed both identified and un-identified needs in a frail older person's population. Further evaluation over time is needed to indicate impact on readmission rate.